2022
DOI: 10.3390/diagnostics12112616
|View full text |Cite
|
Sign up to set email alerts
|

Angiomatoid Fibrous Histiocytoma (AFH) of the Right Arm: An Exceptional Case with Pulmonary Metastasis and Confirmatory EWSR1::CREB1 Translocation

Abstract: Angiomatoid fibrous histiocytoma (AFH) is a rare neoplasm described for the first time by Enzinger in 1979, and classified by World Health Organization 2020 as intermediate malignant potential neoplasm. It mostly occurs in the subcutis and is characterized by varying proportions of epithelioid, ovoid and spindle cells in a nodular and syncytial growth pattern, with some hemorrhagic pseudovascular spaces. In this paper, we report the clinical case of a 62-year-old man who presented with AFH on the right arm, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, it differs from the diagnosis of an angiomatoid fibrous histiocytoma in that LAMTOR1-PRKCD gene fusion is not considered pathognomonic for an aneurysmal fibrous histiocytoma the way EWSR1-CREB1 gene fusion is considered pathognomonic for an angiomatoid fibrous histiocytoma. Jedrych et al relate this to the comparatively fewer reported metastasising aneurysmal fibrous histiocytomas and propose the further examination of gene fusion in such cases [ 7 , 15 , 16 , 18 , 20 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it differs from the diagnosis of an angiomatoid fibrous histiocytoma in that LAMTOR1-PRKCD gene fusion is not considered pathognomonic for an aneurysmal fibrous histiocytoma the way EWSR1-CREB1 gene fusion is considered pathognomonic for an angiomatoid fibrous histiocytoma. Jedrych et al relate this to the comparatively fewer reported metastasising aneurysmal fibrous histiocytomas and propose the further examination of gene fusion in such cases [ 7 , 15 , 16 , 18 , 20 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptom of an aggressive aneurysmal fibrous histiocytoma is an abrupt increase in the tumour size of the initial lesion. Haemorrhage and an ulcerated cutaneous layer were infrequently reported [ 4 , 6 , 7 , 8 , 13 , 15 , 19 , 20 , 23 , 29 ]. However, as of yet, there has not been a comprehensive review attempting to provide standardised diagnostic clinical markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFH lacks a specific immunoprofile, so that immunohistochemistry is supportive rather than diagnostic. Immunohistochemistry variably demonstrates positivity for desmin, CD68 and CD99 5,7,[9][10][11][12] .Lastly, cytogenetic analysis has recently added to the diagnosis of AFH, with the EWSR1-CREB1 fusion gene present in the majority of AFH 5,[8][9][10][11][12] The prognosis of AFH is generally considered to be favorable 2,9-12 but because of its chances of local recurrence ,soft tissue sarcomas should be operated by a specialised surgeon and special consideration should be taken not to miss these tumors preoperatively . There should be wide surgical excision with clear margins.…”
Section: Case Presentationmentioning
confidence: 99%
“…It was first described in 1979 as “angiomatoid malignant fibrous histiocytoma” and it was classified by the World Health Organization under the category of “tumors of uncertain differentiation” in 2020. AFH is a lesion that rarely metastasizes[ 2 - 4 ]. It mostly occurs on the superficial extremities of both children and young adults[ 3 , 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%